2016
DOI: 10.1038/srep39081
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Transcatheter Patent Foramen Ovale Closure for Migraine (EASTFORM) Trial

Abstract: We evaluated the safety and effectiveness of transcatheter patent foramen ovale (PFO) closure for the treatment of migraine in a Chinese population. This non-randomized clinical trial enrolled 258 consecutive substantial or severe migraineurs with a right-to-left shunt (RLS) (grade II–IV) and grouped subjects according to their election or refusal of PFO closure. Migraine was diagnosed according to the International Classification of Headache Disorders III-beta and evaluated using the Headache Impact Test-6 (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 33 publications
(40 reference statements)
0
15
0
3
Order By: Relevance
“…There are clinical trials showing that treatment for right-to-left shunt has not increased responder rate defined as 50% reduction in migraine attacks; however, it has significantly reduced headache days. 11–14 Similarly to the stroke trials, they had initial negative RCTs. With better patient selection and longer follow-up, subsequent trials may show more cessation of migraine headache.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are clinical trials showing that treatment for right-to-left shunt has not increased responder rate defined as 50% reduction in migraine attacks; however, it has significantly reduced headache days. 11–14 Similarly to the stroke trials, they had initial negative RCTs. With better patient selection and longer follow-up, subsequent trials may show more cessation of migraine headache.…”
Section: Discussionmentioning
confidence: 99%
“… 10 There are clinical trials showing that treatment for right-to-left shunt can significantly reduce headache days although the responder rate defined as a 50% reduction in migraine attacks is not different from baseline. 11–14 In addition, the meta-analyses showed that a complete resolution of migraine after treatment for right-to-left shunt occurred in 54% of migraine-with-aura cases and in 39% of migraine-without-aura cases. 15 16 Therefore, right-to-left shunt may be a fundamental cause of migraine.…”
Section: Introductionmentioning
confidence: 99%
“… 35 The MIST trial, along with PREMIUM (Prospective, Randomized Investigation to Evaluate Incidence of Headache Reduction in Subjects With Migraine and PFO Using the AMPLATZER PFO Occluder to Medical Management) and PRIMA (Percutaneous Closure of PFO in Migraine with Aura) trials showed negative results for PFO closure as migraine treatment. 36 ‘PFO closure did not reduce overall monthly migraine days’. 37 …”
Section: New Development Discussionmentioning
confidence: 99%
“…Based on standards reported by Jauss et al ., Wessler et al ., and Xing et al . [7, 15, 16], a five-level categorization system was used in this study based on the appearance of MBs in the TCD spectrum using unilateral MCA monitoring as follows: Grade 0, negative; Grade I, 1 ≤ MBs ≤ 10; Grade II, 10 < MBs ≤ 25; Grade III, > 25 MBs and no curtain; and Grade IV, curtain where a single bubble cannot be identified (Fig 2). …”
Section: Methodsmentioning
confidence: 99%